APLIKASI DONASI PADA TABUNGAN AKHIRAT UMAT BERBASIS WEB DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN PHP MYSQL: Studi Kasus Rumah Yatim dan Tahfidz Qur’an Madani Bandung - Ziani, Asfia; Sumarni, Tarsinah (Melati Institute, 2023)
Rumah Qur'an Madani is currently facing problems in collecting and managing donations from the Community Savings Endowment which are still carried out conventionally. This results in time constraints, lack of transparency, and low accessibility of donors. To overcome this problem, this study proposes the implementation of an efficient, transparent and secure web-based donation application. The system development method used is the Waterfall method with an object-oriented approach using the Unified Modeling Language (UML) as a tool. This web-based donation application will make it easier for donors to donate, improve administrative efficiency, provide better transparency, and expand the scope of donations through increased accessibility and digital marketing. The implementation of this web-based donation application is expected to assist Rumah Qur'an Madani in increasing efficiency, transparency, and expanding the scope of donations.